A DNA segment controlling metal-regulated expression of the Drosophila melanogaster metallothionein gene Mtn. - Otto, E (1987)
Cloned fragments of DNA including the Drosophila melanogaster metallothionein gene Mtn and different amounts of 5' flanking sequences were introduced into flies by P-element-mediated germ line transformation. Comparison of RNA levels in different transformants revealed that metal-regulated and tissue-specific expression of Mtn requires no more than 373 base pairs upstream of the initiation site of transcription. Transformants having an additional, transcribed copy of Mtn could tolerate increased concentrations of cadmium, indicating that Mtn expression is directly related to this phenotype. In separate experiments, these D. melanogaster promoter sequences were fused to the coding sequences of the herpes simplex virus thymidine kinase (TK) gene. After transfection of this fusion into baby hamster kidney cells, increases in TK activity and accumulation of TK RNA were inducible by metals. A series of 5' and 3' deletions showed that D. melanogaster sequences from -130 to -6 were sufficient to confer metal-regulated expression to the TK gene. The function of the D. melanogaster metallothionein promoter in mammalian cells indicates that the mechanism controlling metal regulation is evolutionarily conserved.